Evidence for the indirect effects of perceived public stigma on psychosocial outcomes: The mediating role of self-stigma. (30th June 2016) - Kao, Yu-Chen; Lien, Yin-Ju; Chang, Hsin-An; Wang, Sheng-Chiang; Tzeng, Nian-Sheng; Loh, Ching-Hui
Abstract: This study examined the possible mediating role of self-stigma in the relationship between perceived public stigma and psychosocial outcomes and how this mechanism may be contingent on illness severity in a non-Western (Chinese) sample. A total of 251 participants, namely 151 psychiatric outpatients with psychotic disorders and 100 psychiatric outpatients without psychotic disorders, completed a questionnaire on stigma and psychosocial outcomes that covered topics such as self-esteem, depressive symptoms, and subjective quality of life (QoL). Using a cross-sectional design, ordinary least squares regression and bootstrapping mediation analyses were used to test whether self-stigma mediated the relationship between perceived public stigma and psychosocial outcomes and whether this mediating process was moderated by diagnostic status. The results indicated that self-stigma mediated the effect of perceived public stigma on psychosocial outcomes such as self-esteem, depressive symptoms, and subjective QoL among both patients with psychotic disorders and those without psychotic disorders after controlling for demographic and clinical characteristics. Further, moderated mediation analyses revealed that the indirect effect of perceived public stigma on psychosocial outcomes were not moderated by the status of psychotic diagnoses. Self-stigma might be an essential and tractable target for interventions aimed at breaking the vicious cycle of discrimination and stigmatization toward people with mental illness regardless of their diagnoses. Highlights: Patients with psychoses are stigmatized more severely than those without psychoses. Perceived stigma indirectly influences psychosocial outcomes via self-stigma. Self-stigma is a plausible target for breaking the vicious cycle of discrimination.